Manajemen Public Relations (Humas) Pendidikan Islam: Kajian Tematik Al Quran dan Hadits - Dian Iskandar Jaelani (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
The concept of Public Relations is actually related to the activity of creating understanding through knowledge, and through these activities impacts will emerge. This text will discuss the management of public relationships and how in the Islamic perspective. with the method of tela'ah critical thinking from the author himself. Public Relations combined various imu and included in the ranks of social sciences such as political science, economics, history, psychology, sociology, communication and others. Public Relations also as a propaganda in Islamic teachings that serves as one of the ways to spread effective, efficient and optimal Islamic education.